Application of nanofat grafting to rescue a severe ischaemic hand with thromboangiitis obliterans: A case report about promising salvage procedure. Issue 42 (22nd October 2021) - Ng, Kwan Lok Benjamin; Hsieh, Meng-Chien Willie; Lin, Yun-Nan; Chen, Rong-Fu; Lin, Tsai-Ming; Lin, Sin-Daw; Kuo, Yur-Ren
Abstract: Rationale: Currently, there is no consensus regarding the best treatment for patients with thromboangiitis obliterans (TAO). Regenerative medicine, such as bone marrow stem cells or adipose-derived stem cell (ASC) transplantation, have proven efficacy in improving tissue perfusion and wound healing in clinical trials. In this case, we used nanofat grafting to treat severe conditions in a patient with TAO, with promising outcomes. Patient concerns: This is a case of a 48-year-old smoker who presented with cyanosis in both hands and the right foot, with gangrenous changes. Investigative angiography showed severe vasospasm in the radial and ulnar arteries of the patient's left hand. Progressive cyanosis of the patient's left hand was noted which may eventually require amputation if left untreated. Diagnoses: He was diagnosed with TAO under the Shionoya diagnostic criteria. Interventions: Fasciotomy and necrotic tissue debridement were performed, followed by centrifuged nanofat grafting. The nanofat graft was prepared using Pallua method and deployed with a MAFT-GUN (Dermato Plastica Beauty Co., Ltd., Kaohsiung, Taiwan). Outcomes: Three months later, computed tomography angiography revealed a radial artery patency. The patient's wrist function was preserved with uneventful wound healing. Lessons: The regenerative ability of centrifuged nanofat grafts not only helps wound healing but also helps reverse vasospasm and preserve remnant tissue perfusion.